Interpretative Analysis of Servant Leadership - Tshering, Sangay; Zangmo, Tendi (International Journal of Humanities and Education Development (IJHED), 2022)
This paper has analyzed the leadership style of a recognized leader Mahatma Gandhi of India. His unconventional leadership is studied through the lenses of two theories; Gronn’s theory of leadership as a career and Greenleaf’s servant leadership. It was clear that Gandhi’s leadership was basically nurtured by various systems of the environment and his particular life experiences. His leadership best aligned with all fundamental principles of a ‘servant leadership’ in vision, integrity, modeling, honesty and empowerment of the community for better life and living.